Incidência, prevalência e aspectos clínico-laboratoriais dos pacientes com Síndrome de Sjögren em Cascavel-PR - Leite, Gabriela Fernandes (2022)
Sjögren’s Syndrome (SS) is a chronic systemic autoimmune disease characterized by the inflammatory destruction of exocrine glands, predominantly the salivary and lacrimal glands. The main clinical manifestations are xerostomia (dry mouth) and xerophthalmia (dry eyes). It affects more middle-aged women in a 9:1 ratio. The worldwide incidence of SS varies between 3 and 11 cases per 100,000 individuals, while the prevalence varies between 0.01% and 0.72%. In Brazil, publications with numbers on the manifestation of the disease in the population are rare. This study aimed to estimate the incidence and prevalence of SS, as well as the clinical and laboratory aspects of patients in Cascavel, Paraná, Brazil. It is characterized as an uncontrolled descriptive cross-sectional study. To this end, a search and analysis of medical records of patients diagnosed with SS treated at specialized health services in Cascavel/PR between the years 2000 and 2021 was carried out. Data from medical records were collected in six private rheumatological clinics, in a regional specialty center (Regional Specialty Center of the Intermunicipal Health Consortium of Western Paraná CRE/CISOP), in a municipal specialty center (Specialized Attention Center) and the specialty outpatient clinic of the University Hospital of Western Paraná (HUOP). The second stage of this research consisted of applying a questionnaire to dentists of the Public Health System of Cascavel/PR to assess the degree of knowledge of these professionals about SS. As a result of the first stage, we obtained 64 patients. Of these, 33 live in this city, revealing a prevalence of 9.82 per 100,000 inhabitants, 0.0098%. Among the patients residing in Cascavel diagnosed with SS in 2021, n=8 was obtained, expressing an incidence of 2.38 per 100,000 inhabitants. The data collected showed that 96.8% of the patients were female (p<0.0001). A significant difference was detected between the patients’ age groups (p=0.0003), of which the minimum age found was 21 and the maximum 85 years (mean 48.18 years), and the most predominant age group was between 51 and 59 years old. Regarding clinical characteristics, most patients had xerostomia, xerophthalmia, and osteoarticular pain, while swelling of the salivary glands, vaginal dryness and itching, and Raynaud’s phenomenon was presented in smaller numbers (p<0.0001). 68.8% of the patients had positive ANA in the laboratory tests, and there was a difference between the presence and absence of the tests performed (p=0.0019), with the ANA and anti-La tests influencing the correlation between the four tests performed. Regarding the questionnaires, 35 of the 49 delivered questionnaires were returned, getting a response rate of 71.4%. All questionnaire questions reached more than 50% of correct answers. The questions with more assertive answers were those related to the time and gender most affected, which autoimmune syndromes are most associated with, and present oral manifestations. The behaviors most reported by these professionals are medical referral, guidance on xerostomia, prescription of artificial saliva, and more frequent monitoring of these patients